Carta de compartimentação fisiográfica na escala 1:50.000 a partir da análise integrada na bacia do Ribeirão de Araras (SP) - Rodarte, Fernando do Amaral [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The uncontrolled growth of Brazilian cities and the intense human activities do not have adequate knowledge of the physical environment conditions in its territory, having as consequences many disasters and economic, social and environmental losses. In this context, the land subdivision, through the physiographic or integrated approaches, emerges as an important instrument for Environmental Assessment. Based on this scenario, the developed research had as main objective the development of a Charter of Physiographic subdivision, at the scale 1: 50,000; with individualization of 8 Basic Units of subdivision (UBC's) internally homogeneous but distinct in its surroundings, related to the Lands physiographies, using photointerpretation techniques in aerial photography and GIS. Such techniques in conjunction with indirect (bibliography) and direct (fieldwork) data allowed the development of a standardized cartographic product, easy handling and interpretation. For the application of the method, it was chosen the Basin of Ribeirão de Araras (SP), where it is located the city of Araras (SP). It was found in the urban area, in fluvial plains, the risk of floods, already in agricultural areas was presented susceptible to erosion and in the northeast basin was checked gully. Therefore, the area should be subject to appropriate territorial planning, in order to avoid or minimize the negative impacts. Under the conditions given, it was concluded that the method used, despite it contains the geological variable as predominant, it is open to other areas of professionals for implementation and not only those who have familiarity with geological issues. It is also expected that this research might support both public institutions, researchers and the private sector regarding physiographic information of the Basin of Ribeirão de Araras (SP)

O crescimento desordenado das cidades brasileiras e as intensas atividades antrópicas não tem levado em consideração as condições do meio físico em seu território, tendo como consequências diversas catástrofes e perdas econômicas, sociais e ambientais. Nesse sentido, a Compartimentação de Terreno, por meio da abordagem fisiográfica ou integrada, surge como importante instrumento de Avaliação Ambiental. Com base neste cenário a pesquisa desenvolvida teve como objetivo principal a elaboração de uma Carta de Compartimentação Fisiográfica, na escala 1:50.000; individualizadas em 8 Unidades Básicas de Compartimentação (UBC's), homogêneas internamente, porém distintas em suas adjacências, relacionadas à fisiografia dos terrenos, utilizando técnicas de fotointerpretação em fotografias aéreas e geoprocessamento. Tais técnicas, em conjunto com dados indiretos (bibliografia) e diretos (trabalhos de campo) permitiram a elaboração de um produto cartográfico padronizado, de fácil manuseio e interpretação. Para a aplicação do método foi escolhida a Bacia do ribeirão de Araras, onde está localizado o município de Araras (SP). Verificou-se na área urbana, nas planícies fluviais, o risco de ocorrência de cheias, já nas áreas agrícolas apresentaram locais suscetíveis a processos erosivos e no noroeste da bacia foi verificada a ocorrência de um boçorocamento. Nesse sentido, a área deve ser objeto de adequado planejamento territorial, com o objetivo de evitar ou minimizar os impactos negativos. Nesse sentido, concluiu-se que o método utilizado, apesar de conter a variável geológica como preponderante, é passível de execução por profissionais de outras áreas, desde que possuam uma familiaridade com o técnicas e conceitos a serem utilizados. Espera-se ainda que a presente pesquisa possa dar suporte, tanto aos órgãos públicos, pesquisadores e a iniciativa privada, em relação a informações...
Keywords: Geomorphology; Geomorfologia; Geodinamica; Política ambiental; Araras (SP)